2019
DOI: 10.1177/0961463x18820749
|View full text |Cite
|
Sign up to set email alerts
|

Sequence of practices in personal and societal rhythms – Showering as a case

Abstract: This paper explores methodologically and theoretically how to understand variations in the temporal performances of showering as a practice-as-entity. Time-based data on domestic hot water consumption in 134 Danish households show distinctly different patterns, where some households exhibit highest consumption in the morning and others in the evening. This temporal pattern of showering is analysed based on an innovative combination of statistical cluster analysis and qualitative interviews. Focus is on the tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 39 publications
1
25
1
Order By: Relevance
“…Furthermore, another study within a single country has shown that different types of households have great variation of daily peaks, i.e. some have a marked morning peak, others have a marked evening peak, and a third group have more leveled distribution during the day [11].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Furthermore, another study within a single country has shown that different types of households have great variation of daily peaks, i.e. some have a marked morning peak, others have a marked evening peak, and a third group have more leveled distribution during the day [11].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…This research is focused upon the UK context, in terms of utility governance, infrastructure, supply pressures and social drivers but the authors recognise that there is a larger literature focusing on such issues outside the UK, including [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Some have discussed time-use as the main time related issue [14,19,20,26,28], and some have involved this category in marginal arguments [13,15,17,18,27,30]. The time of use and patterns of activities also have appeared as the main topic [13][14][15]19] as well as the marginal one [20,[26][27][28]. The non-intended result of the time saving or the "time related rebound effect" was mainly discussed by Buhl et al [17], Buhl and Acosta [18], and Jalas [19].…”
Section: Resultsmentioning
confidence: 99%
“…In the next step, the abstracts of the materials were reviewed, and 36 articles within which "time" was a subject matter were selected. Finally, and after assessing the primary selection of articles, 12 articles [13][14][15][17][18][19][20][26][27][28][29][30], which contained some debates and arguments on the roles and uses of the concept of time, were picked for content analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation